Implementation of the Use of Indonesian Language for Foreign Workers - Riana, Rati; Pujiastuti, Endah (STAI Miftahul Ula Nganjuk, 2024)
This study is a qualitative research with descriptive analysis to describe the implementation of the use of Indonesian language for foreign workers at PT Sai Apparel Industries, Semarang. Data was obtained from documents on the implementation of Indonesian language education and training. The research analysis covers the appointment of Indonesian workers as accompanying workers, the implementation of education and training for Indonesian workers in accordance with the qualifications of the positions occupied by foreign workers, and Indonesian language education and training facilities for foreign workers. The results of questionnaires and interviews with management were also analyzed. The results show that at the beginning of its operation in 1998, the management appointed Indonesian workers as assistants to foreign workers, implemented Indonesian language education and training for Indonesian workers in accordance with their qualifications and positions, and facilitated Indonesian language education and training for foreign workers. This is so that foreign workers can transfer knowledge or transfer of know how. Furthermore, the management no longer provides formal Indonesian language education and training. For the practice of using Indonesian, foreign workers learn through google translite, learn from office mates and also practice independently when shopping using Indonesian. Assistants from office staff only observe, monitor, and correct if there are mistakes. Learning by doing, learning by hearing is more effective.